Artesanato e fé : narrativas de uma Mestra Griô sobre romarias e o Santuário de Padre Cícero - Pereira, Cláudia Matos (2014)
This article aims to reflect about the religious phenomenon and the sacred that encompasses the atmosphere of faith and devotion in Juazeiro do Norte, in the state of Ceará, Brazil. Through the embroidered, words woven and the master Griô’s narrative – ‘Dona Fanca’, the pilgrimages and the sanctuary of Padre Cícero demonstrate the look of one who makes from the narratives, its manual work, of witness of faith